INTERACTION OF CONSTITUTIONAL LAW AND INTELLECTUAL PROPERTY RIGHTS IN THE REPUBLIC OF KAZAKHSTAN - Amangeldy Айжан Амангелдіқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The article is devoted to the interaction of intellectual property law with the constitutional law of the Republic of Kazakhstan (hereinafter - RK). The Constitution of the Republic of Kazakhstan proclaims freedom of work and profession, as well as freedom of choice of creativity. Paragraph 1 of Article 20 of the Constitution of the Republic of Kazakhstan states that freedom of creativity is guaranteed. Currently, the scientific research of Kazakhstani scientists does not pay enough attention to the freedom of creativity. The analysis of materials and documents of the Constitutional Court of the Republic of Kazakhstan indicates the absence of a deeper analysis of the constitutional guarantee of freedom of creativity and the limits of this freedom. In addition, there are no provisions on intellectual property in the Constitution of the Republic of Kazakhstan, and the interpretation of norms can only be literal, and we are talking only about freedom of creativity. In this article, the author attempts to show the problems of interaction of intellectual property law with constitutional law, since the relationship between them is deeper than it is reflected in the Constitution of the Republic of Kazakhstan. In the legal literature, most studies of the constitutional and legal regulation of creative relations are reduced only to the objects of copyright, while the freedom of creativity lies in invention, the objective expression of means of individualization. The author has analyzed the concepts of creativity and freedom of creativity and justifies the need for the constitutional consolidation of intellectual property guarantees, to obtain constitutional and legal protection, since it has a significant role in the state policy of the development of the economy of Kazakhstan, expressed in industrialization and the widespread use of digital technologies, which are based on creative intellectual activity. In this regard, it is not enough to establish only a constitutional and legal guarantee of freedom of creativity and labor, it is necessary to include intellectual property norms in the Constitution of the Republic of Kazakhstan, thereby enabling authors and the copyright holder to constitutionally protect their rights and legitimate interests.